The effect of plyometric-training program for 30 days, increasing of explosive and agility strength of basketball players - Artan Kryeziu; Bujar Begu; Fadil Nika (Kazimierz Wielki University, 2018)
The purpose of this research is effect plyometric training program for 30 days in basketball game at explosive strength and agility at basketball players. In this research have participated 20 basketball players from control group (CG n=10) and in experimental plyometric - group (PG n=10) of age 15 + / - 6 months. There are thirteen (13) variables, 3 from anthropometry and 10 motor testes from explosive strength, repeating strength (iterative), flexibility and agility (Bal, B. et al...2011, Asadi, A., etl...2012; Andrejić, O. et la...2012). Plyometric training program is realized according to model of authors Poomsalood, S. Pakulanon, S. (2015). Data processing methods are applied by SPSS version 21.0 which apply the basic statistical parameters and methods for finding significant statistical differences will be the T-test. We may conclude the effect of plyometric-training program for 30 days can be achieved in increasing of explosive strength and agility to basketball players.